4-Aminobenzoic acid as a novel electrolyte additive for improved electrochemical performance of Li1.2Ni0.2Mn0.6O2 cathodes via in situ electrochemical polymerization. (20th January 2020) - Zhuang, Yan; Lei, Yuqin; Guan, Mingyun; Du, Fanghui; Cao, Haishang; Dai, Hui; Zhou, Qun; Adkins, Jason; Zheng, Junwei
Abstract: As Li-rich oxide cathode materials with high capacity suffer from critical-capacity fading during cycling, the proper design of the material interface structure is a very efficient approach for solving such a problem. In this study, 4-aminobenzoic acid is employed as an electrolyte additive to alter the interface properties of Li-rich oxide cathode materials. The cycling stability of Li1.2 Ni0.2 Mn0.6 O2 cathodes is increased enormously by adding 0.25-wt% 4-aminobenzoic acid (4-ABA) in the electrolyte and the capacity retention increases from 61% to 94.4% after 100 cycles. It is demonstrated that 4-ABA is inclined to adsorb onto Li1.2 Ni0.2 Mn0.6 O2 cathode surfaces and then oxidized preferentially at 4.36 V (vs. Li/Li + ), leading to the creation of a polymer film on Li1.2 Ni0.2 Mn0.6 O2 surfaces via in situ electrochemical polymerization. The adsorption and polymerization of 4-ABA generates a protective layer at the interface between the cathode material and electrolyte. As a result, electrolyte decomposition is efficiently suppressed, which reduces the thickness of the solid electrolyte interphase film. It is expected that such an approach involving in situ polymerization of an electrolyte additive to form a protective film could be applicable to various electrode systems for lithium ion batteries. Highlights: The surface of LLC electrode can be modified by 4-ABA adsorption. PABA films are generated by in situ electrochemical polymerization of 4-ABA. The PABA films suppress solvent decomposition, leading to thinner SEI films. Cyclability and rate capability of LLC can be improved by PABA films.